Problematics of Students in Learning English in the Era of the Industrial Revolution 4.0 - Dewi, 1Ratna Sari; Dewi, 1Ratna Sari (International Journal of Psychosocial Rehabilitation, 2020)
Mastery of English is very important for a student, but unfortunately there are still many students who do not realize the need of good mastery of English. Various responses can be found in class related to these problems, especially in the attitude of students during the learning process, student learning outcomes, and participation in carrying out group activities. This study aims to describe the problems faced by students in learning English and its causes. This study uses descriptive research with a questionnaire, observation, and documentation. The results showed that the research subjects had various learning difficulties in English. This happens due to the different levels of English mastery..